Traveling wave analysis of rotating functionally graded graphene platelet reinforced nanocomposite cylindrical shells with general boundary conditions - Qin, Zhaoye; Safaei, Babak; Pang, Xuejia; Chu, Fulei (Results in physics, 2019)
•A unified solution for free vibration analysis of rotating FG-GPLRC cylindrical shells is proposed.•General boundary conditions are represented by using artificial spring techniques.•Effects of boundary spring stiffness, GPL weight fractions, layer number and geometry are evaluated.•Variations of natural frequencies are highly dependent on boundary conditions. This paper studies traveling wave motions of rotating multi-layered functionally graded graphene platelet reinforced composite (FG-GPLRC) cylindrical shell under general boundary conditions. Theoretical equations are obtained according to Donnell shell theory, and artificial spring technique, where centrifugal and Coriolis effects caused by rotation are considered. By employing general orthogonal polynomials using a Gram-Schmidt process as admissible functions, solutions are achieved via Rayleigh-Ritz approach. Then, the accuracy and convergence of solutions are validated by the comparison of the obtained results with those reported in literature. Finally, free vibrations of FG-GPLRC cylindrical shells in both stationary and rotating states are investigated. The influences of boundary spring stiffness, GPL weigh fraction, total layer number, and geometry parameters on shell vibration characteristics are evaluated. It is revealed that the frequency variation trends along with material and geometric parameters are consistent for different boundary conditions, while variation rates and frequency values are highly dependent on boundary spring stiffness.